DESKRIPSI KEMAMPUAN LITERASI MATEMATIS SISWA MADRASAH TSANAWIYAH NEGERI DI KOTA KENDARI - Tandri - Patih (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2019)
Mathematical literacy is the ability to understand and use mathematics in various contexts to solve problems and be able to explain to others how to use mathematics. This study aims to describe the mathematical literacy skills of MTsN students in Kendari City. Data analysis was performed using descriptive statistics, i.e. by tabulating data and graphical methods. The results of the analysis show that overall, the percentage of mathematical literacy abilities of MTsN students in Kendari City is still dominated by groups of low-ability students. Based on the content, students' mathematical literacy ability is still low on content 2. However, based on their categorization, students with a lower category of Mathematical Literacy Abilities are found in content 4. When viewed based on the level, students get the lowest scores on level 6 questions. However, based on the categorization, students with a lower Mathematical Literacy Ability category are found in level 2 and level 4 questions. The school that was used as the object of the study was obtained that both based on the content and level, the mathematical literacy skills of grade IX MTsN 1 Kendari students were better than the IX grade students of MTsN 2 Kendari.